Wideband tympanometry in ears with superior canal dehiscence before and after surgical correction. (1st August 2022) - Velikoselskii, Aleksandr; Papatziamos, Georgios; Smeds, Henrik; Verrecchia, Luca
Abstract: Objectives: Wideband tympanometry (WBT) has been shown to be sensitive to mechanical changes in the ear. This study investigated the effect of surgical correction of superior canal dehiscence (SCD) on WBT (i.e. absorbance and middle ear resonance frequency) compared to those on common surgical outcomes such as symptom resolution, vestibular evoked myogenic potentials (VEMP), and hearing thresholds. Study sample and study design: Seven patients (eight ears with SCD) who underwent surgical correction of SCD underwent WBT in addition to pure-tone audiometry and VEMP assessment. Results: Postoperatively, all ears showed normalised/decreased absorbance at low frequencies and slightly enhanced absorbance in the middle frequency range (7/8 ears). The middle ear resonance frequency, which was initially lower than normal in most patients, increased in 6/8 operated ears, and decreased in two ears with no/partial symptom relief. In comparison, complete symptom control was observed in 6/8 operated ears, VEMP amplitudes reduced or normalised in all ears, and hearing thresholds remained stable or improved in 6/8 ears and worsened in two ears. Conclusions: Surgery seems to change the response to WBT in patients with SCD. The results of WBT may represent mechanical changes induced by SCD, and should be considered when evaluating surgical outcomes.